2015
DOI: 10.1681/asn.2015040411
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the Monocarboxylate Transporter 12 Gene Affects Guanidinoacetate Excretion but Does Not Cause Glucosuria

Abstract: A heterozygous mutation (c.643C.A; p.Q215X) in the monocarboxylate transporter 12-encoding gene MCT12 (also known as SLC16A12) that mediates creatine transport was recently identified as the cause of a syndrome with juvenile cataracts, microcornea, and glucosuria in a single family. Whereas the MCT12 mutation cosegregated with the eye phenotype, poor correlation with the glucosuria phenotype did not support a pathogenic role of the mutation in the kidney. Here, we examined MCT12 in the kidney and found that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 23 publications
(39 reference statements)
4
24
1
Order By: Relevance
“…In a study re‐evaluating the original family, the cause for renal glucosuria accompanying juvenile cataract in all but three family members, was attributed to a second independent heterozygous mutation in the glucose transporter SGLT2/ SLC5A2 rather than the mutation in SLC16A12 . Interestingly, this study revealed an indirect link between the SLC16A12 mutation and reduced guanidinoacetate levels, which is a precursor of creatine but not a substrate of MCT12 70. Thus, there are still many open questions regarding the exact role and function of MCT12 in the kidneys.…”
Section: Ophthalmological Diseasesmentioning
confidence: 78%
“…In a study re‐evaluating the original family, the cause for renal glucosuria accompanying juvenile cataract in all but three family members, was attributed to a second independent heterozygous mutation in the glucose transporter SGLT2/ SLC5A2 rather than the mutation in SLC16A12 . Interestingly, this study revealed an indirect link between the SLC16A12 mutation and reduced guanidinoacetate levels, which is a precursor of creatine but not a substrate of MCT12 70. Thus, there are still many open questions regarding the exact role and function of MCT12 in the kidneys.…”
Section: Ophthalmological Diseasesmentioning
confidence: 78%
“…Table summarizes the substrate specificity, tissue localization, and the potential clinical relevance for the MCT isoforms. It is important to note that the discrepancy between MCT isoform number and SLC16A nomenclature evolved from the order in which each cDNA sequence was determined and characterized .…”
Section: Structure Function Substrate Specificity and Regulationmentioning
confidence: 99%
“…More recently, MCT12 was characterized as a creatine transporter using MCT12 ‐transfected X. laevis oocytes and the utilization of a high‐resolution metabolomics approach . In order to further clarify the association of the MCT12 mutation and its relation to glucosuria, detailed in vitro studies and analysis of patients with the MCT12 mutation were performed . Although individuals with an MCT12 mutation displayed unaltered creatine levels from the wild‐type patients, there was increased renal secretion of creatine's precursor, guanidinoacetate.…”
Section: Structure Function Substrate Specificity and Regulationmentioning
confidence: 99%
See 2 more Smart Citations